HIV, homosexuality and depression – challenges at primary care: a case report - Mohamad, Fadzilah; Lee, Ping Yein; Mawardi, Maliza (Consortium of Islamic Medical Colleges, 2020)
Human Immunodeficiency Virus (HIV) is a chronic lifelong infectious disease that greatly impairs the quality of life. HIV and men who have sex with men (MSM) are seen to be synonyms to each other and both were shown to be the risks for depression. This case report is about a homosexual man who contracted HIV via the MSM activity. Being both homosexual and HIV-infected had given him a lot of negative impacts, stigma and discrimination, which drove him into having major depressive disorder. Having depression with underlying HIV and homosexuality has made this case complicated and challenging, especially when it has to be managed at the primary care level.